Pilgrimage as a New Way to Define and Characterize the Sainthood - Masduki, Anwar (DINIKA : Academic Journal of Islamic Studies, 2018)
Pilgrimage (Ziarah) is one of the common activities done by Indonesian Moslems especially in the tradition of Nahdlatul Ulama (NU), the largest Indonesian Muslim organization in Indonesia. There are many popular pilgrimage destinations in Indonesia specifically in Java such as graves of Walisongo, Kiai, Moslem leaders and many other well-respected persons who have been considered as giving great contributions towards the spread of Islam and its teaching in Indonesia. One of those very well respected persons is Abdurrahman Wahid, commonly known as Gus Dur, the fourth President of the Indonesian Republic from 1999 to 2001 who Passed away in Jakarta on December 30, 2009. His grave has become one of the most favorite and most visited pilgrimage destinations in Indonesia. This article examines the phenomena happened in Tebuireng since the end of 2009, after the death and funeral of Gus Dur. By using Giddens’s social practice perspective, this article found that the recent pilgrimage in Tebuireng has altered and influenced the social life there. This social practice itself involves two basic elements of Giddens’s theory namely; actor and structure to form its social reality. This article highlights the intersection actions between actor and structure and shows how those actions mark a new way the people define and characterize one’s sainthood. The result of research suggests that the pilgrimage phenomena in Tebuireng involve many actors, from lay people to government, from the economic view to religious reason. Those actors have actively engaged in the practice and new consciousness of pilgrimage (as a structure), as a door to recognize someone as Wali.  Keywords:Pilgrimage, Social practice, Sainthood